Manipulation of Cell Physiology Enables Gene Silencing in Well-differentiated Airway Epithelia - Krishnamurthy, Sateesh (Nature Publishing Group, 2012)
The application of RNA interference-based gene silencing to the airway surface epithelium holds great promise to manipulate host and pathogen gene expression for therapeutic purposes. However, well-differentiated airway epithelia display significant barriers to double-stranded small-interfering RNA (siRNA) delivery despite testing varied classes of nonviral reagents. In well-differentiated primary pig airway epithelia (PAE) or human airway epithelia (HAE) grown at the air–liquid interface (ALI), the delivery of a Dicer-substrate small-interfering RNA (DsiRNA) duplex against hypoxanthine–guanine phosphoribosyltransferase (HPRT) with several nonviral reagents showed minimal uptake and no knockdown of the target. In contrast, poorly differentiated cells (2–5-day post-seeding) exhibited significant oligonucleotide internalization and target knockdown. This finding suggested that during differentiation, the barrier properties of the epithelium are modified to an extent that impedes oligonucleotide uptake. We used two methods to overcome this inefficiency. First, we tested the impact of epidermal growth factor (EGF), a known enhancer of macropinocytosis. Treatment of the cells with EGF improved oligonucleotide uptake resulting in significant but modest levels of target knockdown. Secondly, we used the connectivity map (Cmap) database to correlate gene expression changes during small molecule treatments on various cells types with genes that change upon mucociliary differentiation. Several different drug classes were identified from this correlative assessment. Well-differentiated epithelia treated with DsiRNAs and LY294002, a PI3K inhibitor, significantly improved gene silencing and concomitantly reduced target protein levels. These novel findings reveal that well-differentiated airway epithelia, normally resistant to siRNA delivery, can be pretreated with small molecules to improve uptake of synthetic oligonucleotide and RNA interference (RNAi) responses.